AYURVEDIC MANAGEMENT OF DYSLIPIDEMIA W.S.R TO MEDO ROGA: A CLINICAL TRIAL - Vijay Chaudhary; Suraj Negi; Minakshi; Sameet Masand (AYUSHDHARA, 2020)
Obesity is one of the most common disorders of present era giving rise many serious consequences. Excessive intake of food along with stress, lack of exercise, and excess of junk food, canned food, soft drinks, beverages, food containing excessive fat and calories leads to obesity and coronary artery disease. In the present study comparative efficacy of Ayurvedic formulation (Dashang gugglu with Triphaladi Kwatha) was evaluated in a clinical trial to a standard drug i.e., atorvastatin on patients of Medoroga and dyslipidemia. Total 30 patients of obesity and dyslipidemia were registered for the present study and were equally divided in two trial groups. Group I patients were administered with Dashang Guggulu with Triphaladi Kwatha whereas Group II patients were given atorvastatin as control group for a duration of 60 days. Patients were thoroughly assessed on various scientific parameters during complete trial period. The trial drugs showed promising results on dyslipidemia as well as on obesity (reduction of weight). Group I shows promising results in reducing body weight, BMI, skin fold thickness and clinical features however Group II i.e., control group proves to be much effective in improving deranged serum lipid levels. In Group I the mean score of serum cholesterol was 231.41mg/dl which was reduced to 189.08mg/dl with 18.29% reduction. In Group II average value for serum cholesterol was 210.53mg/dl which was reduced to 162.92mg/dl with 22.62% reduction. Group I patients shows 5.60% reduction in BMI while Group II patients shows 2.15% change which means Ayurveda formulation is much more effective than atrovastatin in reducing BMI however difference in two therapies was statistically insignificant. These results prove the efficacy of Ayurvedic formulation in the management of Medoroga.